Effectiveness of the Walking in ScHools (WISH) Study, a peer-led walking intervention for adolescent girls: results of a cluster randomised controlled trial - Marie H. Murphy; S. Maria O'Kane; Angela Carlin; Ian M. Lahart; Leanne C. Doherty; Russell Jago; Gary McDermott; Maria Faulkner; Alison M. Gallagher (BMC, 2024)
Abstract Background Most adolescent girls fail to meet current physical activity guidelines. Physical activity behaviours track from childhood into adulthood and providing adolescent girls with opportunities to be physically active may have health benefits beyond childhood. The effects of walking interventions on adult cardiometabolic health are known, however less is understood about the potential of walking to promote physical activity in adolescents. Following the Walking In ScHools (WISH) feasibility study, this definitive trial aimed to evaluate the effectiveness of a novel, low-cost, school-based walking intervention at increasing physical activity levels of adolescent girls (aged 12-14 years). Methods Female pupils were recruited from eighteen schools across the border region of Ireland and in Northern Ireland. In intervention schools (n = 9), girls aged 15-18 years, were trained as walk leaders, and led the younger pupils in 10-15 min walks before school, at break and lunch recess. All walks took place in school grounds and pupils were encouraged to participate in as many walks as possible each week. The primary outcome measure was accelerometer determined total physical activity (counts per minutes, cpm). Results In total, 589 pupils were recruited to the study. At baseline, pupils engaged in a median (interquartile range (IQR)) 35.7 (21.2) mins moderate-vigorous physical activity (MVPA) per day and only 12% (n = 66) of participants met physical activity guidelines (60 min MVPA per day). The intervention was delivered for a mean (standard deviation (SD)) 19.9 ± 0.97 weeks. The mean post-intervention total physical activity for the intervention group was 676 cpm and 710 cpm in the control group. Post-intervention total physical activity did not statistically differ between groups when adjusted for age, body mass index z-scores and baseline physical activity (mean difference, -33.5, 95% CI = -21.2 to 88.1; p = 0.213). Conclusions 'Scaling-up' physical activity interventions is challenging and despite a promising feasibility study, the results of this fully powered trial suggest that in this context, the WISH intervention did not increase device measured physical activity. Since the COVID-19 pandemic, school environments have changed and although pupils enjoyed the programme, attendance at walks was low, indicating that there is a need to better understand how to implement interventions within schools. Trial registration ISRCTN; ISRCTN12847782; Registered 2nd July 2019.